Los Procesos de Contratación Pública y su incidencia en la declaratoria de contratista incumplido, emitida por la Universidad Nacional de Chimborazo en el año 2014. - Pucha Vizuete, Jessica Carolina (2016)
This legal research work, is made according to four chapters, comprised of the following: In the first chapter, is developed Framework, in which it has raised the issue of the research, besides the objectives aimed at determining how the procurement processes, affect the declaration of contractor defaulted in National University of Chimborazo; and similarly in this chapter we have made justification, by which it has encouraged the research for the realization of this research. The second chapter covers the theoretical framework, which is made up of five units; the first unit studies the Organic Law of the National Public Procurement System and procurement processes; The second unit deals with the contract within the processes of public procurement, in addition to the termination of contracts; Unit Three analyzes the obligations and prohibitions of contractors in public procurement processes, and the reasons why contractors fail to meet their contractual obligations; unit four focuses its analysis on the impact on the declaration of defaulted contractor; and finally, unit five places particular importance to the variables that have been involved in the research process. In the third chapter, has established the methodological framework through which design has been applied, methods and research instruments that have been sued for the development of this thesis, and also has made the determination of the universe population, in order to achieve the necessary data collecting taken to the analysis of the results, to consistently be able to verify the objectives and the hypotheses generated at the beginning of the investigation, to thereby provide the appropriate support and provide the best support of this legal law firm. Finally, concerning the fourth chapter the conclusions and recommendations are presented to complete the research.